Development of a novel fabrication technique for plastic solar cells based on screenprinting - Mercado, Candy C (2005)
An organic solar cell composed of Poly (2-methoxy-5-(2-ethyl-hexyloxy)-1,4-phenylene vinylene) (MEH-PPV) and (6,6)-phenyl C61 ?butyric acid methyl ester (PCBM) was fabricated by screenprinting. This study is part of the worldwide research to drive the cost of PV production down and enable widespread use of the sun?s energy to generate electricity. MEH-PPV, a conjugated polymer, becomes semiconducting upon photodoping wherein loosely bound excitons are produced. Full dissociation of the excitons is not achieved until the polymer is in contact with PCBM, a fullerene derivative. At the interface between the MEH-PPV and PCBM, exciton dissociation happens and a continuous photocurrent is obtained. The device design made use of the bulk heterojunction concept wherein the electron donor (conjugated polymer or MEH-PPV) and the electron acceptor (PCBM) are in a polymer solution. This design maximizes the surfaces between donor and acceptor, thus maximing the dissociation points for the excitons. The bulk heterojunction design and the screenprinting process were possible because of the ability of both MEH-PPV and PCBM to be processed from a solution of Chlorobenzene. Screenprinting experiments showed that the MEH-PPV and PCBM blend has very low viscosity and requires very high print speeds, 300 to 600 mm/s or more, for best film uniformity. Morphology of the screenprinted film is comparable to spincoated films however, macroscopic uniformity as well as the solubility of the PCBM still has to be improved. The screenprinting process was also successfully applied to the etching process of the transparent electrode indium tin oxide (ITO). Screenprinting was also successfully done on flexible PET substrates opening the way to the possibility of a fully screenprinted flexible organic solar cell.
"May 2005."
Thesis (M.S. Materials Science & Engineering) - University of the Philippines Diliman.
Keywords: Solar cells -- Design and construction; Screen process printing